2021
DOI: 10.3390/cancers13184680
|View full text |Cite
|
Sign up to set email alerts
|

Newly-Discovered Neural Features Expand the Pathobiological Knowledge of Blastic Plasmacytoid Dendritic Cell Neoplasm

Abstract: Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a rare and highly aggressive hematologic malignancy originating from plasmacytoid dendritic cells (pDCs). The microRNA expression profile of BPDCN was compared to that of normal pDCs and the impact of miRNA dysregulation on the BPDCN transcriptional program was assessed. MiRNA and gene expression profiling data were integrated to obtain the BPDCN miRNA-regulatory network. The biological process mainly dysregulated by this network was predicted to be neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…This study confirms that HSCT represents the best option to prolong survival and should be pursued as soon as possible, though further efforts are needed to prevent the risk of post‐transplant CNS relapse. Finally, efforts are currently underway to clarify if certain biologic features may be associated with a predisposing neurotropism in ALL, as already documented in blastic plasmacytoid dendritic cell neoplasms with a CNS dissemination 51 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This study confirms that HSCT represents the best option to prolong survival and should be pursued as soon as possible, though further efforts are needed to prevent the risk of post‐transplant CNS relapse. Finally, efforts are currently underway to clarify if certain biologic features may be associated with a predisposing neurotropism in ALL, as already documented in blastic plasmacytoid dendritic cell neoplasms with a CNS dissemination 51 …”
Section: Discussionmentioning
confidence: 98%
“…Finally, efforts are currently underway to clarify if certain biologic features may be associated with a predisposing neurotropism in ALL, as already documented in blastic plasmacytoid dendritic cell neoplasms with a CNS dissemination. 51 …”
Section: Discussionmentioning
confidence: 99%
“… 29 Another hypothesis, as reported in a recent study by Sapienza and co-workers, based on the microRNA expression profile, suggests possible neurogenesis of the neoplastic process. 56 …”
Section: Recommendations and Proposalsmentioning
confidence: 99%
“…These results suggested that a systematic preventive IT chemotherapy was indicated during first-line treatment to prevent CNS relapse and thus lead to a better outcome for patients. More recently, Sapienza et al discovered new neural features by comparing 19 BPDCN patients to 4 normal pDC samples [ 58 ]. They observed 51 deregulated miRNAs in BPDCN samples that significantly influenced neurogenesis.…”
Section: Conventional Therapies and New Therapeutic Options For Bpdcnmentioning
confidence: 99%